Factors influencing the media literacy on community health behaviors practices in Kota Belud Sabah Malaysia - Norhuda Salleh; Emmylia Marry Welly; Noor Aziah Abdullah; Harryizman Harun (Plaridel, 2025)
The perceived importance of media literacy in health discussions has increased significantly. The critical understanding of information is crucial to this role as it has the potential to impact people’s overall well-being and shape individual and societal behaviors. Media literacy involves the ability to access, understand, interpret, and apply information conveyed through various media for the betterment of individuals and communities. However, obtaining health-related information in today’s context can be challenging due to technological advancements. While people may be aware of health issues, translating this awareness into practical behavioral changes for effective health management often remains inconsistent. This study investigates the media literacy level influencing health behavior practices among the Kota Belud community during the COVID-19 pandemic. Through online surveys done on a random sampling of 375 respondents, the study reveals that media literacy directly influences 46.2% of health behaviors related to COVID-19. These behaviors include regular handwashing, mask-wearing, maintaining physical distance, and following recommended health guidelines. The findings show that public comprehension, practical application, and information transmission help match health behaviors with changing social norms.